Ibrohim Muminov and the Contribution of Eastern Philosophy to Uzbek Thought - Yadgarov Begzod, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article analyzes the connections of Ibrohim Muminov with Eastern philosophy and his contribution to Uzbek thought. Muminov absorbed the best traditions of Eastern philosophy in his scientific and philosophical views and applied them to Uzbek thought. The article studies Muminov's scientific research from the perspective of Eastern philosophy, his philosophical system, and their impact on Uzbek social thought. At the same time, the impact of Eastern philosophy on Uzbek thought, its philosophical heritage in connection with its contribution to Uzbek scientific ideas, is considered.